Resolved scaling relations and metallicity gradients on sub-kiloparsec scales at z ≈ 1. Issue 1 (2nd August 2019) - Patrício, V; Richard, J; Carton, D; Péroux, C; Contini, T; Brinchmann, J; Schaye, J; Weilbacher, P M; Nanayakkara, T; Maseda, M; Mahler, G; Wisotzki, L
ABSTRACT: The existence of a spatially resolved star-forming main sequence (rSFMS) and a spatially resolved mass–metallicity relation (rMZR) is now well established for local galaxies. Moreover, gradients with metallicity decreasing with radius seem to be common in local disc galaxies. These observations suggest that galaxy formation is a self-regulating process, and provide constraints for galaxy evolution models. Studying the evolution of these relations at higher redshifts is still, however, very challenging. In this paper, we analyse three gravitationally lensed galaxies at z  = 0.6, 0.7, and 1, observed with MUSE and SINFONI. These galaxies are highly magnified by galaxy clusters, which allow us to observe resolved scaling relations and metallicity gradients on physical scales of a couple of hundred parsecs, comparable to studies of local galaxies. We confirm that the rSFMS is already in place at these redshifts on sub-kpc scales, and establish, for the first time, the existence of the rMZR at higher redshifts. We develop a forward-modelling approach to fit 2D metallicity gradients of multiply imaged lensed galaxies in the image plane, and derive gradients of −0.027 ± 0.003, −0.019 ± 0.003, and −0.039 ± 0.060 dex kpc −1 . Despite the fact that these are clumpy galaxies, typical of high-redshift discs, the metallicity variations in the galaxies are well described by global linear gradients, and we do not see any difference in metallicity associated with the star-forming clumps.